It's gonna take a lot of love to get us through the advertisements - Foskin, Keith Louis, author; Dietemann, David L., advisor; Yust, Dave, 1939-, committee member; Voss, Gary Wayne, committee member; Enssle, Manfred J., committee member (Colorado State University. Libraries, 1989)
My paintings identify and enact the moment when perception, shaped by cultural images collides with experience. Through the recreation of this moment my paintings illuminate unrealistic or stereotypical points of view. They focus on American popular culture's manipulation of image. Each painting acts as a metaphor for my perceptions and challenges the mass media's illusionary and cursory imagery. In content my paintings explore and recreate the paradoxical nature of American popular culture. I imply a sense of contradiction through ambiguous spatial development and the utilization of dichotomous cultural, metaphorical and symbolic images. My painting's formalistic expressiveness suggests that experience can offset American popular culture's manipulation of perception.
Keywords: painting, abstract; mixed media